Analysis of Land Subsidence (Land Subsidence) Affects Against Water Puddle In Semarang City - Pratikso Pratikso; Soedarsono Soedarsono; Andri Kurniawan (International Conference on Coastal and Delta Areas, 2017)
Land subsidence is a natural phenomenon that occurs in the young soil layer (alluvial). The incident is bad for the construction that is above it, it is also exacerbated by the entry of seawater that enters due to the soil surface that has been declining so that the ground elevation is below sea level elevation.Semarang city is one of the cities located in the north of Java island that the condition of the land in the city is alluvial soil. Semarang's coastal topography is flat in the range of 0-2% with most of its area almost equal to sea level and even in some places below it. The results of technical geological investigation in North Semarang city showed that the subsurface layers up to 25 m depth consisted of heavier soil types 1.7-1.84 t / m3, silt with 0.200 0.448, & clay. The predictions of subsidence using the 1D Terzaghi approach with the T90 obtained the smallest decay of 19.6 cm over 8,624 years and the greatest collapse 127.7 cm for 29.634 years, while using the smallest 216 cm subsidence Geostudio program for 8,624 years and the greatest descendant of 135.9 cm for 29.634 years. Keywords: Land Degradation, Digital Elevation Model, Rob's puddle